Living with the land rural and agricultural actors in Twentieth-Century Europe – a Handbook - Grift, Liesbeth van de 1978-; Müller, Dietmar 1969-; Unger, Corinna R. 1978- (Contemporary European history, 2022)
Intro -- Table of Contents -- On the "Contemporary European History" Handbook Series -- 1 Living with the Land: Introduction -- I Working the Land -- 2 Opening Up the Land: Infrastructures in Rural Europe -- 3 Reclaiming the Land: The Drainage Paradigm and the Making of Twentieth-Century Rural Europe -- 4 Developing Rural Regions: Europe in the World -- II Managing Land and Labor -- 5 Mediating Modernity: The Social History of Rural Domestic Education in Northwestern Europe -- 6 Pooling Resources in the European Countryside: Cooperative Models, Rural Capitalism, and Beyond -- 7 Farming under Occupation: Rural Actors and the Social Dynamics of Occupation during World War II -- 8 Transforming Agriculture and Rurality: The Common Agricultural Policy, Actors, National Adaptation and Responses to Policy Challenges -- III Knowing the Land -- 9 Registering Land and Forests: European Institutions and Practices of Landownership -- 10 Experimenting with Scientific Management: New Approaches to Agricultural Labor in the Twentieth Century -- 11 Developing Agriculture, Modernizing Rural Society: Transnational Dimensions of Agricultural Expertise -- IV Organizing Life on the Land -- 12 Representing Peasants and Farmers: Parties, Movements, and Leaders Across Europe -- 13 Governing the Village: Rural Mayors and the Transformations of Self-Government in Europe -- 14 Managing Culture in the European Countryside: The Modern Roots of Rural Traditions -- 15 Challenging Socialist Village Structures: Youth in Rural Regions since 1945 -- List of Contributors -- Index.